Superconducting Receiver Technologies Supporting ALMA and Future Prospects. Issue 5 (6th May 2021) - Uzawa, Y.; Fujii, Y.; Kojima, T.; Kroug, M.; Shan, W.; Ezaki, S.; Miyachi, A.; Kiuchi, H.; Gonzalez, A.
Abstract: This paper describes the development of superconductor–insulator–superconductor (SIS) receivers in the 787–950 GHz radio frequency (RF) range, which covers the highest frequency band of the Atacama Large Millimeter/submillimeter Array (ALMA) and is recognized as the most difficult band in terms of superconducting technology, because the conventional superconducting material of Nb cannot be used for the circuitry in the mixer devices at the frequencies. The development began at the National Astronomical Observatory of Japan (NAOJ) in 2005, and the manufacturing and testing of all the receivers to be installed in the 66 Cassegrain reflector antennas that compose ALMA was completed in 2013. This enabled the terahertz frequency observations with the highest sensitivity from the ground. To meet the stringent ALMA requirements, terahertz SIS mixers with high‐quality superconducting NbTiN films were developed, which successfully demonstrated an unpreceded noise performance less than 230 K (5 times the quantum noise) for all the receivers. After the construction of ALMA, NAOJ began development studies for ALMA enhancement such as wideband and multibeam SIS receivers according to top‐level science requirements. To increase instantaneous bandwidth of the receivers, a submillimeter‐wave multiband receiver concept with a waveguide multiplexer, wideband intermediate frequency SIS‐mixer‐amplifier, and multifrequency local oscillator (LO) source is presented. The multibeam receiver employs a planar‐integrated SIS mixer circuit that includes all the RF components except the LO distribution network and an SIS‐mixer‐based amplifier of low power consumption, which is expected to enable the wide field‐of‐view observations in the future. Key Points: We developed highly sensitive terahertz receivers for the Atacama Large Millimeter/submillimeter Array Seventy‐three receivers with NbTiN‐based superconducting mixers were successfully produced at the National Astronomical Observatory of Japan Next‐generation receivers to enhance the capabilities of the current telescope are being developed